Prototype of the MPSO (Modified Dimension Particle Swarm Optimization) Algorithm Method in Searching for Computer Equipment Data inventory - Nasril Sany; Ari Asmawati; Syafnidawati Syafnidawati (JURNAL SISFOTEK GLOBAL, 2023)
cIn the development of information technology and computerization today, it encourages humans to create systems that can help their lives. Especially in the case of inventory of goods, especially if the location of these items is unknown due to their large number and large and large storage space. The PSO (Particle Swarm Optimazation) algorithm method is a suitable method for dealing with problems, namely searching for inventory data on computer equipment. This method is very useful, especially where the inventory stock of computer equipment is already huge, thousands of them. Especially with the small components. Equipment or computer data whose location was previously unknown, it is hoped that with this PSO algorithm method the inventory can be known which is then put in the data and managed properly. The reporting of computer equipment inventory data can be conveyed properly so that the company management can determine the steps to be taken with the data obtained.